2000
DOI: 10.1046/j.1432-1327.2000.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of creatine kinase by high pressure may precede dimer dissociation

Abstract: The effects of hydrostatic pressure on creatine kinase activity and conformation were investigated using either the high-pressure stopped-flow method in the pressure range 0.1±200 MPa for the activity determination, or the conventional activity measurement and fluorescence spectroscopy up to 650 MPa. The changes in creatine kinase activity and intrinsic fluorescence show a total or partial reversibility after releasing pressure, depending on both the initial value of the high pressure applied and on the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Therefore, as expected, denaturation of the GAPDH implies the loss of enzyme activity. This result is similar to that observed for yeast enolase where the monomers were inactive (6), but slightly different of the creatine kinase dissociation where the inactivation by high pressure may precede dimer dissociation (7).…”
Section: Figsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, as expected, denaturation of the GAPDH implies the loss of enzyme activity. This result is similar to that observed for yeast enolase where the monomers were inactive (6), but slightly different of the creatine kinase dissociation where the inactivation by high pressure may precede dimer dissociation (7).…”
Section: Figsupporting
confidence: 88%
“…Hydrostatic pressure is viewed as a gentle and reversible perturbant, making it a tool very useful to study the dissociation of oligomeric enzymes (5). Recently, in this laboratory, pressure has been used to dissociate yeast enolase and creatine kinase (6,7). Yeast GAPDH was shown to reversibly dissociate into the monomer under pressure (8).…”
mentioning
confidence: 99%
“…This means that the transition observed for GdmCl denaturation corresponds to unfolding, with dissociation occurring silently within the unfolded baseline region. This therefore indicates that unlike many oligomeric proteins (15,26,28,29), high pressure does not induce dissociation of the Ure2 dimer, nor does it induce population of partially-folded intermediates under these experimental conditions. This study suggests that other methods that cause marginal destabilization of Ure2, such as urea (2) or pH (12), could be combined with hydrostatic pressure and thus might provide a useful means of investigating partially folded intermediates of Ure2.…”
Section: Unfolding Of Ure2 By a Combination Of High Pressure And Gdmclmentioning
confidence: 80%
“…A previous study showed that creatine kinase (CK), a dimeric protein of similar size and stability to Ure2, is also relatively resistant to pressure unfolding (26). The application of high pressure caused CK to adopt a partially folded intermediate state, closely resembling the molten globule state populated in moderate concentrations of GdmCl (27).…”
Section: Pressure Denaturation Of Ure2mentioning
confidence: 99%
See 1 more Smart Citation